A STUDY ON SOCIO-ECONOMIC STATUS OF TRIBAL WOMEN IN IDUKKI DISTRICT, KERALA (International Journal of Food and Nutritional Sciences, 2022)
The study conducted in Idukki district, Kerala, delves into the socio-economic status of tribal women. Through an analysis of various factors, this study aims to shed light on the unique challenges and opportunities faced by these women in a predominantly rural and tribal area. The study begins by examining the demographic makeup of Idukki district, providing insights into the total number of inhabitants and the percentage of tribal communities. From there, it delves into the socio-economic factors that have a significant impact on the lives of tribal women, such as education, employment, and health. The study also takes into account the cultural and traditional practices that shape the lives of these women. Through a thorough examination of existing data and surveys, this study highlights the disparities between tribal women in terms of access to education and employment opportunities. It also brings attention to the challenges faced by these women in accessing quality healthcare and basic amenities. Furthermore, this study looks into the role of government policies and initiatives in addressing the socio-economic issues faced by tribal women in Idukki district. This study provides a comprehensive overview of the socio-economic status of tribal women in Idukki district, shedding light on the unique challenges and opportunities present in their lives. The findings of this study can serve as a valuable resource for policymakers, organizations, and individuals looking to understand and support the empowerment of tribal communities in Kerala.